Inquiry ability of students to develop cognitive ability in learning hydrostatic pressure - Sylvia Dewi, Pramita; Cahya Prima, Eka; Widodo, Ari; Rochintaniawati, Diana (Insitut Pendidikan Indonesia, 2023)
This research aims to implement questions through problem stimuli regarding hydro static pressure based on inquiry investigations. This research is limited to conducting experiments because the focus of the study is analyzing the cognitive abilities of the questions tested on 106 junior high school students. This study uses a quantitative exploratory method that aims to improve the understanding that students go through for their initial inquiry and perspective abilities during the science learning process. Data collection was carried out using a test instrument in the form of description questions whose inquiry indicators had been developed referring to the National Research Council (NRC) indicators, plus a questionnaire to identify students’ perceptions as a secondary data source. The results showed that all stages of inquiry activities had a low percentage of 50.0%. The involvement of students has yet to be able to ask investigative questions in formulating problems to be a significant start, as well as predicting in hypothesising. So it affects the activities of designing experiments and analysing data. This causes scientific reasoning to be challenging to communicate. In comparison, student interest in science learning is only around 51.2%. This proves that the inquiry process aspects are tied to one another, and the role of students must be maximally fully involved in every stage. Teacher and technology support needs to be harmonised to optimise further research.